Divine Iconoclasm and the Making of Sacred Space in John Capgrave’s Life of Saint Katherine of Alexandria - Yun Ni (Religions, 2025)
The polemics of idol worship in John Capgrave’s Life of Saint Katherine of Alexandria have been interpreted by previous scholars as either the author’s engagement with the Lollard image controversy or a political critique of Henry VI. This essay, however, shifts the focus from Katherine and her iconoclasm to the concept of divine iconoclasm, defined here not only as the divinely sanctioned or divinely motivated destruction of religious images but also as God’s direct intervention to dismantle false representations and correct human perceptions of the divine. It further argues that Capgrave’s Life redefines sacred space as primarily constructed through light, emphasizing its immateriality and exposing the saint’s physical limitations. In these scenarios, divine iconoclasm emerges as a constructive force that resolves the tension between the secular and the sacred. Moreover, Christ’s celestial manipulation of the vision of sacred space and the relationship between body and space—encouraging confidence while discouraging self-inflation—serves as a model for how a monarch should inspire both love and fear. In this way, Capgrave’s Mirrors for Princes is embedded within his hagiography, where the image debate features prominently, addressing the heated political and theological controversies of his time. By combining these elements, the essay bridges two strands of criticism that have previously treated the political and theological dimensions of the text separately.